Proceedings of the 5th International Congress on Sport Sciences Research and Technology Support 2017
DOI: 10.5220/0006601401450150
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Exergaming - Feasibility and Benefits of Physiological Adaptation for Cardiorespiratory Training in Older Adults by Means of Smartwatches

Abstract: Exergames are videogames that use physical movement to mediate player's interactions with digital contents. Multiple adaptation mechanisms have been used to enhance the effectiveness of employing Exergames to promote physical exercise. One of the most interesting strategies utilizes physiological signals to infer the status of player's cardiorespiratory responses and create real-time game adaptations. This strategy is called biocybernetic-adaptation and despite its promising potential, quantitative studies ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is well established that increased heart rate (HR) and myocardial oxygen consumption during exercise result from increased sympathetic stimulation [11,12]. Recent advances in human-computer interaction, specifically in the field of physiological telemetry, have allowed heart rate variability (HRV) analysis to be a cornerstone of monitoring the effectiveness of physical exercise through exergame [13]. Using short-term Fourier transform time-frequency analysis, recent investigations have shown that HRV decreases following moderate to high-intensity exercise [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that increased heart rate (HR) and myocardial oxygen consumption during exercise result from increased sympathetic stimulation [11,12]. Recent advances in human-computer interaction, specifically in the field of physiological telemetry, have allowed heart rate variability (HRV) analysis to be a cornerstone of monitoring the effectiveness of physical exercise through exergame [13]. Using short-term Fourier transform time-frequency analysis, recent investigations have shown that HRV decreases following moderate to high-intensity exercise [14].…”
Section: Introductionmentioning
confidence: 99%